Novel Vein Patterns in Arabidopsis Induced by Small Molecules. Issue 1 (16th November 2015) - Carland, Francine; Defries, Andrew; Cutler, Sean; Nelson, Timothy
Abstract : Numerous compounds inducing leaf vein pattern defects target auxin biology. Abstract: The critical role of veins in transporting water, nutrients, and signals suggests that some key regulators of vein formation may be genetically redundant and, thus, undetectable by forward genetic screens. To identify such regulators, we screened more than 5000 structurally diverse small molecules for compounds that alter Arabidopsis ( Arabidopsis thaliana ) leaf vein patterns. Many compound-induced phenotypes were observed, including vein networks with an open reticulum; decreased or increased vein number and thickness; and misaligned, misshapen, or nonpolar vascular cells. Further characterization of several individual active compounds suggests that their targets include hormone cross talk, hormone-dependent transcription, and PIN-FORMED trafficking.